Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Pada BPJS Kesehatan Manado - Melsa Sonia Iryanti Ronsumbre; Tonny Maringka; Farly Teneh (Journal of Mandalika Literature, 2025)
This study aims to test the impact of Work Discipline on Employee Performance at BPJS Kesehatan Manado. Using simple linear regression analysis, the research examines the relationship between levels of work discipline and employee performance at the institution. Data collected through questionnaires were analyzed to determine the extent to which work discipline contributes to employee performance. The results show a regression coefficient of 0.362, indicating that each one-unit increase in work discipline is associated with a 0.362- unit improvement in employee performance. The t-statistic of 3.555 with a significance level of less than 0.001 demonstrates that the relationship between work discipline and employee performance is statistically significant. These findings underscore the importance of work discipline in enhancing employee performance at BPJS Kesehatan Manado. The study provides valuable insights for management in improving systems and policies related to work discipline to boost overall employee performance.